An AIEgen-based 3D covalent organic framework for white light-emitting diodes - Huimin Ding (Nature Portfolio, 2018)
3D covalent organic frameworks (COF) show interesting hierarchical arrangements of nanopores and open sites but their synthesis remains challenging. Here the authors report a fluorescent AIEgen-based 3D COF and demonstrate application as a coating material for white LEDs and for sensing of picric acid